Evaluation of tolerance to phosphorus shortage in cowpea (Vigna unguiculata L. Walp) in Cuba.. I. nutritive solution culture. - Gómez, Luis A. (2006)
Phosphorus deficiency is a major limitingfactor for symbiotic nitrogen fixation and grain yield oflegume crops in the tropics. Eight cowpea genotypes of wideuse in Cuba, were grown in hydroponics solutions; supplyingfrom 50 to 500 µM of P/plant/week. Nitrogen nutrition wasdependent upon symbiotic N2-fixation on adding of 4mmoles NO3/plant/week. Shoot growth was severely limitedby P deficiency, while dry weight of roots increased in bothgroups of plants. Nodule formation was severely decreasedby P deficiency, while specific nodule activity was increasedin the atmospheric N2 fixing plants. Growth response of N2plants was higher than that of NO3- fed plants due to P useefficiency, and revealed a the great large N2-fixationpotential of the specie.